2007
DOI: 10.1523/jneurosci.0254-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

A Subpopulation of Olfactory Bulb GABAergic Interneurons Is Derived from Emx1- and Dlx5/6-Expressing Progenitors

Abstract: The subventricular zone (SVZ) of the postnatal brain continuously generates olfactory bulb (OB) interneurons. We show that calretinin ϩ , calbindin ϩ , and dopaminergic (TH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
301
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(328 citation statements)
references
References 49 publications
24
301
0
3
Order By: Relevance
“…2, available at www.jneurosci.org as supplemental material). Consistent with the predominantly embryonic origin of calbindinϩ neurons (De Marchis et al, 2007) (but see Kohwi et al, 2007), this subset was consistently ␤-galactosidasenegative (supplemental Fig. 2a, available at www.jneurosci.org as supplemental material).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…2, available at www.jneurosci.org as supplemental material). Consistent with the predominantly embryonic origin of calbindinϩ neurons (De Marchis et al, 2007) (but see Kohwi et al, 2007), this subset was consistently ␤-galactosidasenegative (supplemental Fig. 2a, available at www.jneurosci.org as supplemental material).…”
Section: Resultssupporting
confidence: 60%
“…These studies revealed that between 10 and 30,000 cells are generated per day (Alvarez-Buylla et al, 2001;Cameron and McKay, 2001) and that about half of these die within the first 4 weeks (Petreanu and Alvarez-Buylla, 2002;Kempermann et al, 2003;Lemasson et al, 2005). Whereas some studies suggested that most cells that survived initial 4 weeks could still be detected after several months (Kempermann et al, 2003;Lemasson et al, 2005), others reported a further decrease in the number of labeled neurons during 365 d of survival (Petreanu and Alvarez-Buylla, 2002;Kohwi et al, 2007). Extrapolating these data from labeling a single or few cohorts would suggest a considerable contribution of adultgenerated neurons to the OB network, leading several studies to propose an increase in the size of the dentate gyrus (DG) and the OB attributable to adult neurogenesis (Kempermann et al, 2003;Merson et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our in vivo results, the ratio of TH + neurons to Tubb3 + neurons was also increased in dissociated cell cultures prepared from the OB of E16.5 Gnao −/− mice, whereas the ratio of CB + neurons to Tubb3 + neurons was decreased. Given that TH + and CB + neurons originate from a common progenitor pool in the dorsal lateral ganglionic eminence during the embryonic period and CR + neurons are derived from progenitor cells located elsewhere (38), it is likely that the reciprocal changes in the number of TH + cells and CB + cells in the OB of Gnao −/− mice are attributable to altered cell-type specification rather than to 6. Model for the roles of the VNO and MOE in the response of male mice to pheromones.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies demonstrate that, at any postnatal age, at least 50% of the NG2 + cells in the SVZ are proliferative and that Cdk2 is a major molecular regulator of their proliferation throughout postnatal development (Belachew et al, 2002;Jablonska et al, 2007). The results of our previous studies also defined the following cellular and molecular properties of NG2 + cells in the SVZ Jablonska et al, 2007): i) NG2 + cells are found scattered through the wall of the lateral ventricle, but they are more abundant in the anterior SVZ; ii) NG2 + cells in the SVZ constitute approximately 12% and 3% of the total cell population at P8 and P30-60, respectively; iii) NG2 + cells in the SVZ are highly proliferative, as demonstrated by the percentages of NG2 + Ki67 + cells in the SVZ -56 and 32% at P8 and P30, respectively; iv) NG2 + cells of the SVZ express cellular markers of neural progenitor cells and stem cells, including the Lewis X antigen (LeX) (Capela and Temple, 2003), and the transcription factors Mash1, Olig2, and Dlx (Doetsch et al, 2002;Parras et al, 2004;Marshall et al, 2005;Menn et al, 2006;Kohwi et al, 2007;Parras et al, 2007); and v) NG2 + cells of the SVZ display a type-C cell phenotype, including expression of the EGFR, PSA-NCAM, and nestin (Capela and Temple, 2002;Doetsch et al, 2002). Consistent with our findings, other reports have also described the presence of NG2 + cells in the SVZ, and demonstrated diverse cellular and molecular properties of these progenitors in this neurogenic region, including co-expression of DCX Tamura et al, 2007), responsiveness to sonic hedgehog (Loulier et al, 2006), and Islet-1-induced migration into striatum (Rogelius et al, 2006).…”
Section: Discussionmentioning
confidence: 99%